Endopelvic cup migration in the presence of concomitant infection and pseudoaneurysm of the external iliac artery - Radaelli, Alessandra; Orlandini, Luca; Melchiorre, Fabio; Massa Saluzzo, Cesare; Ravasi, Flavio Rinaldo (Lo Scalpello - Journal, 2025)
Endopelvic migration of the acetabular prosthetic component is an uncommon but serious complication in hip replacement. When the medial acetabular wall is perforated, intrapelvic injuries may occur. In such cases, the external iliac artery and bladder are the most commonly involved structures. In this case three main sources of potential problems that emerge from preoperative assessment must be taken into account: presence of infection with periprosthetic collection, significant lymphedema in the lower extremities complicated by the presence of ulcerative lesions in both legs, and vascular involvement with the presence of a pseudoaneurysm of the external iliac artery. In order to minimize the surgical risks presented by explanation of the prosthesis, interventional angiography should be conducted, which can reveal the previously undiagnosed pseudoaneurysm and allow positioning of a covered stent to protect the vessel. Placement of a vascular covered stent before explanation of the acetabular component offers a two-fold advantage: i.e. to secure this important blood vessel before surgery and allow a less invasive approach, which is of particular relevance when taking into account the precarious situation of soft tissues.